Schaum's outline of theory and problems of microprocessor fundamentals - Tokheim, Roger L. ([S.l.] : Mcgraw-Hill, 1989)
A new expanded edition of this very successful Schaum's Outline. It is updated and revised to keep up with the technology of the 8-bit processor, about which courses will still be taught in the vocational-technical schools for the near future. An important inclusion in this edition is the 8-bit 6502 processor. For the advanced or 2nd level digital-electronics course of the two-year market. Hundreds of solved and supplementary problems are included.